Efficacy of V4HR Newcastle Disease (V4HR-ND) Vaccine in Broiler Birds in Bangladesh - Rahman, M.B.; Rahman, M.M.; Rahman, M.; Kabir, S.M.L.; Nazir, K.H.M.N.H.; Amin, M.M. (International Journal of Poultry Science, 2004)
Thirty day-old chicks of Cobb-100 breed with the history of vaccination of parent stock against Newcastle disease (ND) were equally divided into two groups such as group A and B. At 7 days of age of birds, group A was vaccinated with experimentally prepared V4HR-ND vaccine via eye drop @ 106.0EID50/bird to determine the efficacy of this vaccine while group B was kept as unvaccinated control. The birds were used for the study during the period from October 2003 to December 2003. Each bird of group A was boostered with same vaccine @ same dose at 24 days of age. Both the groups (A and B) were challenged after two weeks of post-booster vaccination with 0.25ml inoculum containing 105.0EID50 of virulent field isolates of ND virus intramuscularly. The results of challenge experiment revealed that six birds (40%) of group A succumbed within 3 to 4 days of post-challenge, whereas 15 (100%) unvaccinated control birds of group B showed clinical illness and ultimately died within 3 to 5 days. Thus, the experimental V4HR-ND vaccine conferred 60% protection of vaccinated birds against challenge infection. The mean values of Haemagglutination inhibition (HI) antibody titres of birds in group A were found to have significantly (P